(untitled) (Research, Society and Development, 2020)
Beech (Fagus sylvatica) is one of the main forest species in Europe and one of the main problems in the cultivation of these species is the occurrence of disease caused by Phytophthora plurivora. Studies in the literature shows phosphites as a good alternative for the control of diseases caused by oomycetes. However, the mode of action is still being studied. This work aimed to evaluate the commercial product based on potassium phosphite Phytogard® on the control of disease caused by P. plurivora in beech plants and to understand the possible mode of action of the product on this pathogen. Beech plants were sprayed with different concentrations of Phytogard® and then inoculated with the pathogen. We evaluated the diseases incidence, water uptake and the amount of pathogens DNA in the host roots. In in vitro experiments, mycelial growth, production of fresh mycelium and zoospores by this pathogen were determined. We also evaluated the electrolyte leakage, lipid peroxidation and the β-1,3-glucanase activity in the mycelium. It was also evaluated the hyphae morphology from mycelium treated or not with Phytogard® by using scanning electron microscopy. The results showed that in all concentrations of Phytogard® preventively controls diseases caused by P. plurivora in beech plants. The Phytogard® inhibited mycelial growth and zoospore production by P. plurivora. Furthermore, the product modified the hyphae morphology, changed membrane permeability and mycelium cell wall synthesis in the pathogens.